2018
DOI: 10.1111/1365-2745.12976
|View full text |Cite
|
Sign up to set email alerts
|

The cover uncovered: Bark control over wood decomposition

Abstract: 1. Woody debris (WD) represents a globally significant carbon stock and its decomposition returns nutrients to the soil while providing habitat to microbes, plants and animals. Understanding what drives WD decomposition is therefore important.2. WD decomposition rates differ greatly among species. However, the role of bark in the process remains poorly known.3. We ask how, and how much, interspecific variation in bark functional traits related to growth and protection have afterlife effects on the decompositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
68
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 96 publications
(139 reference statements)
1
68
0
1
Order By: Relevance
“…Consistent with our results, many previous studies have found that bark decomposes faster than wood (Maser & Trappe, 1984; McColl & Powers, 2003; Shorohova et al, 2008a; Zhang & Zak, 1998). However, other studies have shown the opposite (Dossa et al, 2018; Ganjegunte et al, 2004; Tarasov & Birdsey, 2001). The effect of bark presence on underlying wood decomposition is also mixed, with either slower (Dossa et al, 2018) or faster (Ulyshen et al, 2016) wood decomposition, or no effect of bark removal (Oberle et al, 2017).…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Consistent with our results, many previous studies have found that bark decomposes faster than wood (Maser & Trappe, 1984; McColl & Powers, 2003; Shorohova et al, 2008a; Zhang & Zak, 1998). However, other studies have shown the opposite (Dossa et al, 2018; Ganjegunte et al, 2004; Tarasov & Birdsey, 2001). The effect of bark presence on underlying wood decomposition is also mixed, with either slower (Dossa et al, 2018) or faster (Ulyshen et al, 2016) wood decomposition, or no effect of bark removal (Oberle et al, 2017).…”
Section: Discussionmentioning
confidence: 91%
“…The effect of bark presence on underlying wood decomposition is also mixed, with either slower (Dossa et al, 2018) or faster (Ulyshen et al, 2016) wood decomposition, or no effect of bark removal (Oberle et al, 2017). Differences in bark and wood decomposition rates, and the impact of bark on wood decomposition are likely influenced by species identity (Dossa et al, 2016), wood diameter and bark attachment (Dossa et al, 2018), moisture (Ulyshen et al, 2016), plant defence compounds in bark (Ganjegunte et al, 2004), nutrient availability, access to the environment and susceptibility to fragmentation. Below we discuss how N, access to the environment and susceptibility to fragmentation influence bark and wood decomposition dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations